Propuesta arquitectónica para el Parque Ambiental Municipal, Pérez Zeledón - Navarro-Díaz, Dagoberto de Jesús (Instituto Tecnológico de Costa Rica., 2019)
Life is conditioned to the ecosystems and biodiversity, they provide the necessary resources for the life development. There are many studies that indicate a transformation in ecosystems that causes biodiversity loss. Conservation process requires social participation, so it is necessary to use tools for dissemination and environmental education to generate social empowerment. In this case, the Municipality of Pérez Zeledón, in search of environmental protection has taken the initiative to use a property as a tool for education and environmental enjoyment of people from the Canton. This proposal intends to provide infrastructure solutions for administration an attention to park visitors in order to promote environment education and wildlife conservation. For the development of the proposal two analogous cases are analyzed, then the physical-environmental characteristics of the site are studied, finally, the result of the architectural proposal for the Municipal Environmental Park in Pérez Zeledón is obtained, which has three modules; environmental interpretation, wildlife rescue and social extension.
Proyecto de graduación (Licenciatura en Arquitectura y Urbanismo) Instituto Tecnológico de Costa Rica, Escuela de Arquitectura y Urbanismo, 2019.
Keywords: Costa Rica, Perez Zeledón; Parques -- Medio ambiente; Educación ambiental; Medio ambiente -- Conservación